Extension of Shelf Life of Roasted Duck by combination of Vacuum Packaging and Low Temperature Storage - Mita Sinhamahapatra (Archives of Current Research International, 2024)
A study was conducted to assess the shelf life of roasted duck under aerobic and vacuum packaging and in refrigerator (4±1° C) and freezer (-18±1° C) storage. The samples were analyzed for moisture content, pH, Thiobarbituric Acid (TBA) Value, Tyrosine value, Total Plate Count (TPC), Total Psychrophilic Count (TPSC), Yeast and Mould Count (YMC), colour, flavour and tenderness. The products showed an increasing trend in pH, TBA value, tyrosine value, TPC, TPSC and YMC during the storage period in refrigerated and freezer temperatures irrespective of the packaging methods i.e. aerobic and vacuum, whereas, the moisture content, colour, flavor and tenderness of the product followed a declining trend during storage. Though the sensory parameter scores declined during storage, but these changes were less in the vacuum packed and frozen products. The study showed that the aerobically packed roasted duck was acceptable upto 7th day and vacuum packed roasted duck was acceptable upto 14th day in the refrigerated storage. The freezer storage extended the shelf life of the roasted duck till 40th day in aerobic packaging while the combination of freezer storage and vacuum packaging extended the shelf life of the roasted duck till 60th day. These findings have significant implications for the food industry, enabling the development of strategies to extend the shelf life of roasted duck and reduce food waste.